Stress and Depression in the Workplace of Educators in the Philippines - Orlanda-Ventayen, Caren; Ventayen, Randy Joy (International Journal of Occupational Safety and Health, 2022)
Introduction: Workplace stress and depression should be properly treated to maintain productivity in teaching. Unmanaged stress and depression could lead to severe outcomes that affect the environment in the classroom. Thus, managing stress and preventing depression in the workplace are significant aspects of successful teaching. Methods: This study aims to determine the level of workplace stress and depression of the educators in the Philippines by gathering their demographic profiles, levels of workplace stress, and the level of depression. A correlation was used if there is a significant difference in the profile between workplace stress and a state of depression. This research study used the descriptive survey method with educators as respondents in the questionnaire during the school year 2019-2020 with a total of 407 respondents. Results: Based on the study results, teachers disagree that they experience stress in the workplace, and teachers seldom experience depression. The difference shows that the level of stress and depression are lower at vocational and college levels. Conclusion: Based on the findings, teachers should understand how to practice stress management and prevent depression. School administrators and policymakers should look at possible interventions to minimize the level of stress and depression of educators.